Integrative Genetic Variation, DNA Methylation, and Gene Expression Analysis of Escitalopram and Aripiprazole Treatment Outcomes in Depression: A CAN-BIND-1 Study - Islam, Farhana; Lisoway, Amanda; Oh, Edward S.; Fiori, Laura M.; Magarbeh, Leen; Elsheikh, Samar S. M.; Kim, Helena K.; Kloiber, Stefan; Kennedy, James L.; Frey, Benicio N.; Milev, Roumen; Soares, Claudio N.; Parikh, Sagar V.; Placenza, Franca; Hassel, Stefanie; Taylor, Valerie H.; Leri, Francesco; Blier, Pierre; Uher, Rudolf; Farzan, Faranak; Lam, Raymond W.; Turecki, Gustavo; Foster, Jane A.; Rotzinger, Susan; Kennedy, Sidney H.; Müller, Daniel J. (Pharmacopsychiatry, 2024)
Introduction Little is known about the interplay between genetics and epigenetics on antidepressant treatment (1) response and remission, (2) side effects, and (3) serum levels. This study explored the relationship among single nucleotide polymorphisms (SNPs), DNA methylation (DNAm), and mRNA levels of four pharmacokinetic genes, CYP2C19, CYP2D6, CYP3A4, and ABCB1, and its effect on these outcomes.Methods The Canadian Biomarker Integration Network for Depression-1 dataset consisted of 177 individuals with major depressive disorder treated for 8 weeks with escitalopram (ESC) followed by 8 weeks with ESC monotherapy or augmentation with aripiprazole. DNAm quantitative trait loci (mQTL), identified by SNP-CpG associations between 20 SNPs and 60 CpG sites in whole blood, were tested for associations with our outcomes, followed by causal inference tests (CITs) to identify methylation-mediated genetic effects.Results Eleven cis-SNP-CpG pairs (q<0.05) constituting four unique SNPs were identified. Although no significant associations were observed between mQTLs and response/remission, CYP2C19 rs4244285 was associated with treatment-related weight gain (q=0.027) and serum concentrations of ESCadj (q<0.001). Between weeks 2-4, 6.7% and 14.9% of those with *1/*1 (normal metabolizers) and *1/*2 (intermediate metabolizers) genotypes, respectively, reported ≥2 lbs of weight gain. In contrast, the *2/*2 genotype (poor metabolizers) did not report weight gain during this period and demonstrated the highest ESCadj concentrations. CITs did not indicate that these effects were epigenetically mediated.Discussion These results elucidate functional mechanisms underlying the established associations between CYP2C19 rs4244285 and ESC pharmacokinetics. This mQTL SNP as a marker for antidepressant-related weight gain needs to be further explored.
Keywords: antidepressant; depression; escitalopram; aripiprazole; methylation; quantitative trait loci